Odpowiedzi

  • Użytkownik Zadane
2010-03-04T18:00:34+01:00
Wyznacz X.
a(x+t)=m //:a
x+t=m/a
x=m/a-t

a(x-b)/n=3t //*n
a(x-b)=3tn //:a
x-b=3tn/a
x=3tn/a +b

ax/b-t=m //(b-t)
ax=m(b-t)
a=m(b-t)/x

k/x=w //*x
k=wx
x=k/w

x-a/b=m/k
x=m/k+a/b

x/n+a/b=t
x/n=t-a/b
x=n(t-a/b)

h/x-m=t
h/x=t+m
x=(t+m)/h

x-a/b=3x-x/k
x-a/b=x(3-1/k) //:x
1-ax/b=(3-1/k) //*b
b-ax=b(3-1/k)
-ax=b(3-1/k)-b
x=-[b(3-1/k)-b]/a
Najlepsza Odpowiedź!
2010-03-04T18:06:39+01:00
A(x+t)=m
ax+at=m /-at
ax=m-at/:a
x=m-at i wszystko podzielić przez a, ułamek

a(x-b)/n=3t
ax-ab/n=3t/*n
ax-ab=3t*n/+ab
ax=3t*n+ab/:a
x=3t*n+ab i wszystko podzielić przez a, ułamek

ax/b-t=m
ax/b-t=m/*b-t
ax=m*(b-t)/:a
x=m*(b-t) i wszystko podzielić przez a, ułamek

k/x=w
k/x=w/*x
k=w*x/:w
k/w=x

x-a/b=m/k
x-a/b=m/k/+a/b
x=m/k + a/b

x/n+a/b=t/+a/b
x/n=t+a/b/*n
x=t+a/b*n

h/x-m=t/+m
h/x=t+m/*x
h=t+m*x/:t+m
x= h/t+m

x-a/b=3x-x/k/*k
x-a/b*k=3x-x
x-a/b*k=2x/-x
a/b*k=x

bardzo prosze :) pozdrawiam